2017
DOI: 10.1177/1090198117742440
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Contribution of the Built Environment on Obesity Among New York State Students

Abstract: Different patterns of food consumption may explain varying determinants of obesity between younger and older students. Regional variations in local associations between the built environment variables and obesity may suggest differences in how healthy food sources are accessed locally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
0
22
0
2
Order By: Relevance
“…A recent ecological study from New York found that FFO were positively associated only among middle/high school students (seventh and 10th school grades combined) while greater density of farmer's markets within the school districts were negatively associated with obesity rates only among younger students (pre-kindergarten/kindergarten, second and fourth combined). 24 We found that only two studies reported associations separately by relative socio-economic advantage. These studies found some evidence of greater positive associations between food environments near schools and obesity among children and school-neighbourhoods at greater socio-economic disadvantage.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A recent ecological study from New York found that FFO were positively associated only among middle/high school students (seventh and 10th school grades combined) while greater density of farmer's markets within the school districts were negatively associated with obesity rates only among younger students (pre-kindergarten/kindergarten, second and fourth combined). 24 We found that only two studies reported associations separately by relative socio-economic advantage. These studies found some evidence of greater positive associations between food environments near schools and obesity among children and school-neighbourhoods at greater socio-economic disadvantage.…”
Section: Discussionmentioning
confidence: 78%
“…However, there is a need for future studies in more diverse settings. A recent ecological study from New York found that FFO were positively associated only among middle/high school students (seventh and 10th school grades combined) while greater density of farmer's markets within the school districts were negatively associated with obesity rates only among younger students (pre‐kindergarten/kindergarten, second and fourth combined) …”
Section: Discussionmentioning
confidence: 99%
“…One study measured the number of produce stands/farmers' markets within 0.4/0.8/1.6/8‐km radii straight‐line buffer around home 28 . Other studies created buffer zones with different radii and around either homes or schools: Two studies used a 0.4‐km radius straight‐line buffer around schools 22 or homes, 28 and another two used a 0.4‐km radius road‐network buffer around schools 30 or homes 10 ; three used a 0.8‐km radius road‐network 31 or straight‐line 26,28 buffer around homes; two used a 1.0‐km radius road‐network 29 and straight‐line 32 buffer around homes; and two used a 1.6‐km radius straight‐line buffer around home, 28,29 and another two used a 1.6‐km radius road‐network around home or school 10,21 …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, obesity is a risk factor for acne, which implies that types and numbers of restaurants around the residential and work location of people could be related to their obesity. A number of studies in the US ( 139 ), New York ( 105 ), Utah ( 106 ), the UK ( 13 , 140 ), Porto ( 104 ), New Orleans ( 141 ), and China ( 142 ) showed higher fast food restaurant density was significantly associated with higher obesity rates among students. Therefore, an increased number of fast food restaurants near the address may increase the risk of obesity, which may indirectly affect the occurrence of acne.…”
Section: Discussionmentioning
confidence: 99%
“…At present, a growing number of studies have focused on the impact of built environment on health (Table 4 in Appendix), especially those chronic diseases such as obesity (13), cardiovascular disease (15) and mental health (14). Studies indicated that obesity was positively associated with population density and the availability of fast-food outlets from the people's residence (104)(105)(106)(107)(108). Moreover, other studies also found the incidence of cardiovascular disease was significantly higher with more fast-food outlets than areas with no fast-food outlets (15,109).…”
Section: Built Environmental Factorsmentioning
confidence: 99%